2008
DOI: 10.1186/1475-2875-7-112
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism patterns in Duffy-binding protein among Thai Plasmodium vivax isolates

Abstract: Background: The Duffy-binding protein II of Plasmodium vivax (PvDBPII) has been considered as an attractive target for vaccine-mediated immunity despite a possible highly polymorphic nature. Among seven PvDBP domains, domain II has been shown to exhibit a high rate of nonsynonymous polymorphism, which has been suggested to be a potential immune (antibody binding) evasion mechanism. This study aimed to determine the extent of genetic polymorphisms and positive natural selection at domain II of the PvDBP gene am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 26 publications
5
55
0
Order By: Relevance
“…The remaining two glycan variants were designed to shield polymorphic residues in PvDBP but retain exposure of proposed interaction surfaces for DARC binding and/or PvDBP dimerization (Figures 1 and 2). There are at least 36 polymorphic positions in PvDBPII [28], [29], but many sequence variants are extremely rare (Figure S2). The majority of polymorphic residues are dimorphic and localized to subdomain 2 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining two glycan variants were designed to shield polymorphic residues in PvDBP but retain exposure of proposed interaction surfaces for DARC binding and/or PvDBP dimerization (Figures 1 and 2). There are at least 36 polymorphic positions in PvDBPII [28], [29], but many sequence variants are extremely rare (Figure S2). The majority of polymorphic residues are dimorphic and localized to subdomain 2 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…P. vivax dependence on DARC for invasion and its restrictive preference for reticulocytes supports PvDBP vaccine development. However, the rapid kinetics of parasite invasion (less than one minute) [26], [27] combined with PvDBP polymorphism [28], [29] pose challenges for vaccine development that may be addressable by the rational redesign of PvDBPII for improved immunogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…H1.T1, H3.T1, H3.T2, H3.T3 and M3.T1 epitopes are the variant strain among Thai vivax isolates [19]. NI is the target epitopes of non-inhibitory antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…The highest frequency of polymorphism was found in residues D384G, R390H, L424I, W437R and I503K [19]. The phylogenetic analysis of dbpII Thai P. vivax isolates demonstrated that most Thai isolates shared distinct alleles with P. vivax isolates from different geographical areas with some allele groups so far unique to Thailand [19]. Since DBPII polymorphisms among Thai isolates are extensive and some are unique, understanding naturally protective antibody against DBPII needs to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous and widespread polymorphisms have been identified in Plasmodium invasion ligands, specifically PfEBA-175 and Plasmodium vivax Duffy-binding protein (PvDBP) (17)(18)(19). In contrast, only four polymorphic mutants have been identified in RII PfEBA-140, all of which are present in the F1 domain: I185V, N239S, K261R/K261T, and K285E (11).…”
mentioning
confidence: 99%